(untitled) (Research, Society and Development, 2020)
Objective: To identify, within the literature, the impacts of Parkinson’s Disease (PD) on individuals. Method: The methodology used for the elaboration and development of this work was the Integrative Literature Review of works with an approach about PD. Results: PD causes motor and non-motor changes that can result in the progression of disabilities and a decrease in the individual’s autonomy. The instability of the disease and the fact that it is incurable constitute a difficult reality to be faced for the rest of life, as well as a limiting factor of daily actions, which imposes on the individual with the disease becoming dependent on others for carrying out their routine activities, causing a decrease in the quality of life of these people. Conclusion: Therefore, PD is among the degenerative diseases of the nervous system that express the failure of neurological, irreversible devices, and, for this reason, they are peculiarly sensitive to aging, requiring assessment tools to diagnose the degree of the disease. The patient finds himself, especially with regard to motor impairments, which prevent patients from enjoying their independence.